Pengaruh Kode Klasifikasi Usia Program Siaran Televisi Terhadap Sensor Mandiri Orang Tua Pada Tontonan Anak : (Survei Pada Orang Tua Wali Murid MI Muhammadiyah Leuwiliang) - Dissa Nur Adilla; Amin Shabana (Lembaga Pengembangan Kinerja Dosen, 2023)
Television programming has a profound impact on the formation and development of behavior in people of all ages. Understanding the age categorization code for television broadcast programs and practicing self – censorship on television broadcast programs are two ways to prevent the occurrence of harmful influences. The purpose of this study is to determine the extent to which the age classification code for television broadcast programs influences parents' self – censorship of their children's viewing. This study employs a quantitative methodology using survey methods. Random sampling was utilized to acquire sample data, and questionnaires were used to collect data. The findings of this study indicate that the age categorization code of television broadcast shows has a favorable influence on parents' self – censorship of their children's viewing.